Rapid Molecular Diagnosis of Tuberculosis and Its Resistance to Rifampicin and Isoniazid with Automated MDR/MTB ELITe MGB® Assay - Vichita Ok; Alexandra Aubry; Florence Morel; Isabelle Bonnet; Jérôme Robert; Wladimir Sougakoff (MDPI AG, 2021)
The MDR/MTB ELITe MGB® kit (ELITech) carried on the ELITe InGenius® platform is a new real-time PCR assay allowing automated extraction and detection of DNA of the Mycobacterium tuberculosis complex (MTB) and mutations in the rpoB and katG genes and inhA promoter region (pro-inhA) associated to resistance to rifampicin and isoniazid, the two markers of multidrug-resistant TB (MDR). We assessed the performances of the test on a collection of strains (n = 54) and a set of clinical samples (n = 242) from routine practice, comparatively to TB diagnosis and genotypic drug susceptibility testing (gDST) as references. Regarding the 242 clinical samples, the sensitivity and specificity of MTB detection by ELITe were 90.9% and 97.5%, respectively. For the detection of resistance-conferring mutations on positive clinical samples, we observed perfect agreement with gDST for katG and pro-inhA (κ = 1.0) and two discordant results for rpoB (κ = 0.82). Considering the 54 cultured strains, very good agreement with gDST was observed for the detection of the 25 distinct mutations in rpoB, katG, and pro-inhA, (κ = 0.95, 0.88, and 0.95, respectively). In conclusion, the automated MDR/MTB ELITe MGB® assay shows great promise and appears to be a valuable tool for rapid detection of pre-MDR- and MDR-TB directly from clinical specimens.